2016
DOI: 10.1136/heartjnl-2016-309746
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal strain combined with delayed-enhancement magnetic resonance improves risk stratification in patients with dilated cardiomyopathy

Abstract: Combining GLS and LGE could be useful for risk stratification and prognostic assessment in patients with DCM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 35 publications
1
34
0
6
Order By: Relevance
“…Global longitudinal strain. GLS is an early and sensitive marker of LV functional decline over a wide range of diseases (15)(16)(17). In cancer patients receiving chemotherapy, an early LVEDD and LVESD: Left ventricular end-diastolic and end-systolic diamerters, respectively; LV: left ventricular; RV: right ventricular; LVEF: left ventricular ejection fraction; TAPSE: tricuspid annular plane systolic excursion; LAVI: left atrial volume indexed to body surface area; Mitral E, dt, Ea and Ee': Mitral inflow early diastolic velocity, declaration time of the early inflow, the ratio between early inflow and late inflow velocities and the ratio between early mitral inflow velocity and averaged pulsed tissue Doppler early diastolic velocities derived from basal anterior, septal, posterior and lateral LV walls, respectively; IVC and cIVC: inferior vena cava maximal diameter and its variation, respectively.…”
Section: Changes In Apical Strain In the Follow-up According To Brementioning
confidence: 99%
“…Global longitudinal strain. GLS is an early and sensitive marker of LV functional decline over a wide range of diseases (15)(16)(17). In cancer patients receiving chemotherapy, an early LVEDD and LVESD: Left ventricular end-diastolic and end-systolic diamerters, respectively; LV: left ventricular; RV: right ventricular; LVEF: left ventricular ejection fraction; TAPSE: tricuspid annular plane systolic excursion; LAVI: left atrial volume indexed to body surface area; Mitral E, dt, Ea and Ee': Mitral inflow early diastolic velocity, declaration time of the early inflow, the ratio between early inflow and late inflow velocities and the ratio between early mitral inflow velocity and averaged pulsed tissue Doppler early diastolic velocities derived from basal anterior, septal, posterior and lateral LV walls, respectively; IVC and cIVC: inferior vena cava maximal diameter and its variation, respectively.…”
Section: Changes In Apical Strain In the Follow-up According To Brementioning
confidence: 99%
“…It has been widely reported that GLS in conjunction with HF stage classification is more useful for HF patient management than conventional echocardiographic parameters, even in patients with findings other than Stage A HF [13]. The utility of GLS for HF patients is accounted for by its ability to predict independently associated with long-term outcome [30]. They also found that patients with GLS ≥8.3%…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been shown that LV longitudinal myocardial function, rather than a global LV function such as LVEF, can be a more accurate marker for detection of subtle changes in LV myocardial function as well as a more accurate prognostic marker. [23][24][25] It was further reported that LV dispersion, which reflects the heterogeneity of timing of regional LV myocardial contraction, plays an important role by serving as a prognostic marker for HF patients independent of LVEF. 26,27 However, what the association is of LV dispersion with LV performance in patients with ASD remains uncertain.…”
Section: Bi-ventricular Interaction In Asd Patients After Asomentioning
confidence: 99%